2004
DOI: 10.1007/s00122-004-1738-1
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of anthracnose (Colletotrichum spp.) resistance in a cross between Capsicum annuum and C. chinense

Abstract: Anthracnose fruit rot is an economically important disease that affects pepper production in Indonesia. Strong resistance to two causal pathogens, Colletotrichum gloeosporioides and C. capsici, was found in an accession of Capsicum chinense. The inheritance of this resistance was studied in an F(2) population derived from a cross of this accession with an Indonesian hot pepper variety ( Capsicum annuum) using a quantitative trait locus (QTL) mapping approach. In laboratory tests where ripe fruits were artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 9 publications
(6 reference statements)
1
75
0
1
Order By: Relevance
“…Hence, the inheritance of these traits has been extensively studied and the quantitative trait loci (QTLs) that contribute to disease resistance and fruit traits have been reported (Ben Chaim et al, 2001a, 2001bLefebvre et al, 2003;Minamiyama et al, 2005Minamiyama et al, , 2007Popovsky and Paran, 2000;Thabuis et al, 2003;Voorrips et al, 2004). In addition to the above-mentioned traits, axillary shooting, flowering date, primary axis length, and number of leaves are also important for pepper production.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the inheritance of these traits has been extensively studied and the quantitative trait loci (QTLs) that contribute to disease resistance and fruit traits have been reported (Ben Chaim et al, 2001a, 2001bLefebvre et al, 2003;Minamiyama et al, 2005Minamiyama et al, , 2007Popovsky and Paran, 2000;Thabuis et al, 2003;Voorrips et al, 2004). In addition to the above-mentioned traits, axillary shooting, flowering date, primary axis length, and number of leaves are also important for pepper production.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a recessive gene controlling anthracnose resistance has also been described in Capsicum chinense (Pakdeevaraporn et al, 2005). Voorrips et al (2004) used quantitative trait loci (QTL) mapping and identified a highly significant main QTL with major effect on three evaluated traits (frequency of infection, lesion true diameter and overall diameter of lesion) after the inoculation of C. gloeosporioides in plants from crosses between Capsicum annuum and C. chinense. In this study, tests to assess resistance were performed only in ripe fruit.…”
mentioning
confidence: 99%
“…Disease evaluation was conducted using the disease incidence (percentage of infected sites per total inoculated sites), overall lesion diameter (averaged over all inoculation points, including those that did not develop lesions), and true lesion diameter (averaged over all lesions that actually developed) method at 7 days after inoculation (DAI), as described previously (Voorrips et al 2004). A chi-squared goodness-of-fit test was used for statistical analysis.…”
Section: Disease Evaluationmentioning
confidence: 99%
“…In these countries, the causal pathogens are C. gloeosporioides, C. capsici, and C. acutatum. The primarily causal pathogens in Thailand and Indonesia are C. gloeosporioides and C. capsici (Lin et al 2002, Voorrips et al 2004. C. gloeosporioides attacks pepper fruits at both the green and red stages, while C. capsici mainly attacks pepper fruits at the red stage (Park et al 1990a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation